An Overview on Mushroom Polysaccharides: Health-promoting Properties, Prebiotic and Gut Microbiota Modulation Effects and Structure-function Correlation - Araújo-Rodrigues, Helena; Sousa, Ana Sofia; Relvas, João Bettencourt; Tavaria, Freni K.; Pintado, Manuela (Carbohydrate polymers, 2024)
Mushroom polysaccharides are recognized as “biological response modifiers”. Besides several bioactivities, a growing interest in their prebiotic potential has been raised due to the gut microbiota modulation potential. This review comprehensively summarizes mushroom polysaccharides' biological properties, structure-function relationship, and underlying mechanisms. It provides a recent overview of the key findings in the field (2018–2024). Key findings and limitations on structure-function correlation are discussed. Although most studies focus on β-glucans or extracts, α-glucans and chitin have gained interest. Prebiotic capacity has been associated with α-glucans and chitin, while antimicrobial and wound healing potential is attributed to chitin. However, further research is of utmost importance. Human fecal fermentation is the most reported approach to assess prebiotic potential, indicating impacts on intestinal biological, mechanical, chemical and immunological barriers. Gut microbiota dysbiosis has been directly connected with intestinal, cardiovascular, metabolic, and neurological diseases. Concerning gut microbiota modulation, animal experiments have suggested proinflammatory cytokines reduction and redox balance re-establishment. Most literature focused on the anticancer and immunomodulatory potential. However, anti-inflammatory, antimicrobial, antiviral, antidiabetic, hypocholesterolemic, antilipidemic, antioxidant, and neuroprotective properties are discussed. A significant overview of the gaps and research directions in synergistic effects, underlying mechanisms, structure-function correlation, clinical trials and scientific data is also given. [Display omitted] •Direct and gut microbiota-related effects of mushroom polysaccharides (MP)- chitin, α- and β-glucans.•Further structural research is mandatory to robust structure-function correlations.•MP promote gut metabolite production, impacting the heart, liver, and brain axis.•MP impact intestinal biological, mechanical, chemical and immunological barriers.•β-glucans exhibit a strong immunomodulating, antioxidant and metabolic regulation effect.